The essential oil of the leaves of Verbesina macrophylla (Cass.) S.F.Blake has antimicrobial, anti-inflammatory and antipyretic activities and is toxicologically safe. (30th January 2021) - de Veras, Bruno Oliveira; de Oliveira, João Ricardhis Saturnino; de Menezes Lima, Vera Lúcia; do Amaral Ferraz Navarro, Daniela Maria; de Oliveira Farias de Aguiar, Júlio César Ribeiro; de Medeiros Moura, Geovanna Maria; da Silva, José Wellinton; de Assis, Caio Rodrigo Dias; Gorlach-Lira, Krystyna; de Assis, Priscilla Anne Castro; de Souza Barbosa, Jorge Irapuan; de Melo, Maria Rita Cabral Sales; et al.
Abstract: Ethnopharmacological relevance: Verbesina macrophylla (Cass.) S.F.Blake is a medicinal plant from South America, popularly known as "asa de peixe", "asa de peixe branco", "cambará branco" or "cambará guaçu", being used by traditional communities for its healing powers in the form of teas, infusions, liqueurs and extracts, for the treatment of bacterial and fungal infections of the urinary and respiratory tracts, such as kidney problems, bronchitis, inflammation and fever. However, none of the ethnopharmacological properties has been scientifically evaluated. Aim of the study: Based on the ethnopharmacological use of the species, this study investigated the chemical composition, and for the first time acute toxicity, hemolytic, antimicrobial, anti-inflammatory and antipyretic activities of the essential oil from leaves of V. macrophylla . Material and methods: The essential oil was obtained from the leaves by hydrodistillation (HD), being characterized by gas chromatography coupled to mass spectrometry (GC-MS) and gas chromatography coupled to flame ionization detection (GC-FID). The antimicrobial activity was evaluated by the broth microdilution technique in bacteria and fungi that cause infections of the respiratory and urinary tract, and toxicological safety regarding hemolytic activity on human red blood cells (hRBCs), and acute toxicity in mice. The anti-inflammatory activity was evaluated by the model carrageenan-induced peritonitis with quantification of the levels of TNF-α and IL-1β in the intraperitoneal fluid, and ear edema induced by croton oil. The antipyretic activity evaluated in mice with pyrexia induced by yeast. Results: The extraction of essential oil by hydrodistillation (HD) showed a yield of 0.33 ± 0.04%, with its composition constituted mainly by sesquiterpenes of hydrocarbons (94.00%). The essential oil demonstrated antibacterial and antifungal activity, with a low rate of hemolysis in human red blood cells (hRBCs) and no clinical signs of toxicity were observed in animals after acute treatment, which suggested that the LD50 is greater than 5000 mg/kg; p.o. The essential oil demonstrated anti-inflammatory activity reducing levels of pro-inflammatory cytokines TNF-α (38.83%, 72.42% and 73.52%) and IL-1β (37.70%, 75.92% and 87.71%), and ear edema by 49.53%, 85.04% and 94.39% at concentrations of 4, 40 and 400 mg/kg, respectively. The antipyretic activity presented by the essential oil is statistically similar to dipyrone. Conclusion: The set of results obtained, validates the main activities attributed to the traditional use of Verbesina macrophylla (Cass.) S.F.Blake. These data add industrial value to the species, considering that the antimicrobial, anti-inflammatory and antipyretic activities present results similar to the drugs already used also presenting safety. The results suggest that essential oil from V. macrophylla may be used by industry for the development of drugs with natural antimicrobial, anti-inflammatory and antipyretic effect. Graphical abstract: Image 1